Assessment of Photovoltaic-Based Controlled Environment Agriculture as a Viable Solution for Enhancing Energy efficiency, Profitability, and Environmental Sustainability in Major Cities - Guoqing Hu; Fengqi You (Chemical Engineering Transactions)
Controlled environment agriculture (CEA) offers a promising approach for sustainable food production by mitigating the impacts of climate variability and ensuring consistent yields. This study explores the integration of solar photovoltaic (PV) systems into CEA facilities across the ten most populous cities in the United States. Our comprehensive assessment indicates that, on average, 25.7 % of the energy consumption in these facilities can be offset by solar PV systems, significantly enhancing environmental sustainability. This integration has the potential to reduce carbon emissions by 0.658 CO2 eq-kg/m², primarily due to decreased transportation needs associated with imports. However, these benefits are accompanied by increased costs, with operational expenses rising by approximately 18% due to the installation of solar panels. Additionally, PV-based CEA facilities contribute to a 5 % increase in light pollution due to the reliance on artificial lighting and result in nitrification, averaging 0.77 NH3 eq-kg/m². The variation in local energy, environmental, and economic policies across different cities and states leads to significant differences in the benefits and costs associated with PV-based CEA systems. This study aims to inform local policy development to better support the application of PV-based CEA facilities, ultimately advancing environmental sustainability targets in urban agriculture.